North Korea: A Totalitarian and Nuclear Relic - Abad Quintanal, Gracia (Razón y fe, 2018)
A year ago, in December of 2011, Kim Jong Il passed away. He was the «Eternal president» of North Korea but nothing seems to have improved in this punished and backward Republic. Due to its absolute, despotic and corrupt criteria, its political system doesn’t know anything about human rights. Therefore its madness for owning nuclear weapons leaves a large proportion of the rural population completely immersed in the lack of prospects and permanent source of food.